Enzyme catalysis prior to aromatic residues: Reverse engineering of a dephospho-CoA kinase - Makarov, Mikhail; Meng, Jingwei; Tretyachenko, Vyacheslav; Srb, Pavel; Březinová, Anna; Giacobelli, Valerio Guido; Bednárová, Lucie; Vondrášek, Jiří; Dunker, A Keith; Hlouchová, Klára (Protein science, 2021)
The wide variety of protein structures and functions results from the diverse properties of the 20 canonical amino acids. The generally accepted hypothesis is that early protein evolution was associated with enrichment of a primordial alphabet, thereby enabling increased protein catalytic efficiencies and functional diversification. Aromatic amino acids were likely among the last additions to genetic code. The main objective of this study was to test whether enzyme catalysis can occur without the aromatic residues (aromatics) by studying the structure and function of dephospho-CoA kinase (DPCK) following aromatic residue depletion. We designed two variants of a putative DPCK from Aquifex aeolicus by substituting (a) Tyr, Phe and Trp or (b) all aromatics (including His). Their structural characterization indicates that substituting the aromatics does not markedly alter their secondary structures but does significantly loosen their side chain packing and increase their sizes. Both variants still possess ATPase activity, although with 150-300 times lower efficiency in comparison with the wild-type phosphotransferase activity. The transfer of the phosphate group to the dephospho-CoA substrate becomes heavily uncoupled and only the His-containing variant is still able to perform the phosphotransferase reaction. These data support the hypothesis that proteins in the early stages of life could support catalytic activities, albeit with low efficiencies. An observed significant contraction upon ligand binding is likely important for appropriate organization of the active site. Formation of firm hydrophobic cores, which enable the assembly of stably structured active sites, is suggested to provide a selective advantage for adding the aromatic residues.
Keywords: fosfotransferasy s alkoholovou skupinou jako akceptorem; Bacterial Proteins; Amino Acid Substitution; Catalytic Domain; Phosphotransferases (Alcohol Group Acceptor); Catalysis; Mutagenesis, Site-Directed; Aquifex; Protein Structure, Secondary; substituce aminokyselin; sekundární struktura proteinů; mutageneze cílená; katalytická doména; katalýza; bakteriální proteiny